1980
DOI: 10.1103/physrevlett.44.136
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Rb-Xe131Spin-Exchange Cross Section inXe

Abstract: Estimates of the Rb-131 Xe spin-exchange cross section have been obtained by observing the nuclear spin relaxation of 131 Xe in the presence of a Rb vapor. Nuclear spin relaxation of 131 Xe due to the presence of a foreign buffer gas and the relaxation rate on the glass walls of the cell have also been observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1982
1982
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…Although excessive RbH buildup on the cell entry window will reduce laser irradiation, deposition on other cell surfaces may not necessarily adversely affect the achievable noble gas spin polarization. Previous work demonstrated that the 131 Xe T 1 relaxation time increases for this spin I = 3/2 isotope because of RbH buildup (48)(49)(50). RbH surface coating may therefore also reduce the 83 Kr T 1 relaxation rates and improve SEOP.…”
mentioning
confidence: 94%
“…Although excessive RbH buildup on the cell entry window will reduce laser irradiation, deposition on other cell surfaces may not necessarily adversely affect the achievable noble gas spin polarization. Previous work demonstrated that the 131 Xe T 1 relaxation time increases for this spin I = 3/2 isotope because of RbH buildup (48)(49)(50). RbH surface coating may therefore also reduce the 83 Kr T 1 relaxation rates and improve SEOP.…”
mentioning
confidence: 94%
“…(b) The silicon chip footprint is 3 cm  1 cm, with a thickness of 1 mm. The dimensions of the pump and probe chambers are 5 mm  5 mm  1 mm and 3 mm  3 mm  1 mm, respectively, whereas the channel connecting the pump and probe chambers is 1 mm  0. magnetometers 13,18,19 sensitive to magnetic fields along the y-axis as defined in Fig. 1a, we detected the 129 Xe magnetization, and thus its polarization 20 129 Xe longitudinal polarization along the z-axis into the transverse x-y plane with a transverse DC magnetic field pulse, as shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Grover (1978) detected the polarization enhancement of the heavier noble gases in the presence of polarized Rb using Rb as a magnetometer. Continuing this work, Volk et al (1980) recognized the effect of long-lived van der Waals molecules in the spin-exchange process, produced and destroyed in a three body process including N 2 , but largely overestimate the cross-section for binary processes. The first quantitative determination of the xenon polarization, and of the efficiency of the polarization transfer is due to Bhaskar et al (1982).…”
Section: Introductionmentioning
confidence: 85%